A risk-based modelling approach to enhance shipping accident investigation - Celik, Metin; Lavasani, Seyed Miri; Wang, Jin (Elsevier BV, 2010)
This paper developed a risk-based modelling approach to enhance the execution process of shipping accident investigation (SAI). Specifically, the paper addressed a fuzzy extended fault tree analysis (FFTA) that combines the effects of organizational faults and shipboard technical system failures under a unique risk assessment scheme. The case study illustrates that a novel idea behind the proposed methodology allows relevant accident investigators to clarify the probability of technical failures, operational misapplications, and legislative shortages leading to the shipping accident. The current SAI reports can be extended with an integrated risk assessment section to formulate integrated strategies along with risk control measures onboard ships. Since the consequences of shipping accidents are still a global concern, the paper addresses integration of a FFTA into SAI reports to ensure a consistent database and subsequent decision aid to accident analysis and prevention efforts in the maritime transportation industry.